Síntese, caracterização e estudo de nanômeros de silício como reforço mecânico em resinas acrílicas a base de PMMA - Lourenço, Rodrigo Vinicius (Universidade Federal de São Carlos, 2014)
The search for improvements in material properties has been studied extensively and fabrication of polymeric nanocomposites stands out for having excellent mechanical properties. In this work, silicon nanomers were prepared by solgel process and grafted in a poly(methyl methacrylate) (PMMA) matrix by powderliquid polymerization, a very common process in prosthodontic procedures to polymerize acrylic resins. Two different types of nanomers were prepared: nanoparticles of silicon dioxide (NPs SiO2) from the tetraethylorthosilicate (TEOS) as precursor and molecules of polyhedral oligomeric silsesquioxane (POSS) from the methyl trimethoxysilane (MTMS), both using the silane coupling agent 3-(trimetoxisilil) propyl methacrylate (TMSPM) also as precursor. The nanomers were produced at different concentrations and embedded in the polymeric matrix after 1 and 7 days to form the PMMA/SiO2 and PMMA/POSS nancomposites. They showed different mechanical behavior with respect to present concentration in the matrix, for PMMA/SiO2 nanocomposites best results were obtained for flexural strength, flexural modulus, yield strength and surface microhardness at low concentrations (less than 1%), while PMMA/POSS with about 1,5% presented better results for flexural strength, flexural modulus and microhardness. In addition, there was a decline to almost all the observed results for the nanocomposites prepared after 7 days compared to those prepared after 1 day, regardless of nanomer and concentration.
Synthesis, characterization and study of silicon nanomers as mechanical reinforcement in PMMA-based acrylic resins.
Keywords: Polímeros; Prótese dentária; Sol-gel; Nanopartículas; SiO2; CIENCIAS EXATAS E DA TERRA::QUIMICA